2004
DOI: 10.1593/neo.04142
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiles in Stage I Primary Non Small Cell Lung Cancer Using Comparative Genomic Hybridization Analysis of cDNA Microarrays

Abstract: To investigate the genomic aberrations that are involved in lung tumorigenesis and therefore may be developed as biomarkers for lung cancer diagnosis, we characterized the genomic copy number changes associated with individual genes in 14 tumors from patients with primary non small cell lung cancer (NSCLC). Six squamous cell carcinomas (SQCAs) and eight adenocarcinomas (ADCAs) were examined by high-resolution comparative genomic hybridization (CGH) analysis of cDNA microarray. The SQCAs and ADCAs shared common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 49 publications
9
67
0
Order By: Relevance
“…For example, genomic copy number and protein levels of KCIP-1 were previously found to be amplified and overexpressed in primary lung cancers by cDNA clonebased CGH array analysis (Jiang et al, 2004) and proteomic analysis (Chen et al, 2002), respectively. Our functional genomic approach, which integrates simultaneous CGH, transcript microarrys, proteomic analyses, and siRNA, allows us not only to quickly identify potential oncogenes but also to explore their significance as diagnostic and therapeutic targets in tumor progression -more than could be achieved by any technique alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, genomic copy number and protein levels of KCIP-1 were previously found to be amplified and overexpressed in primary lung cancers by cDNA clonebased CGH array analysis (Jiang et al, 2004) and proteomic analysis (Chen et al, 2002), respectively. Our functional genomic approach, which integrates simultaneous CGH, transcript microarrys, proteomic analyses, and siRNA, allows us not only to quickly identify potential oncogenes but also to explore their significance as diagnostic and therapeutic targets in tumor progression -more than could be achieved by any technique alone.…”
Section: Discussionmentioning
confidence: 99%
“…Now, HER-2 aberrations are used as a predictor of response to therapy, and treatment of HER-2-positive breast cancer with the monoclonal anti-HER-2 antibody trastuzumab has been shown to improve prognosis (Ross and Fletcher, 1999). Emerging evidence of common amplicons in lung adenocarcinomas (Luk et al, 2001;Jiang et al, 2004;Tonon et al, 2005) suggests that additional oncogenes remain to be identified; however, conventional techniques are ineffective in pinpointing such oncogenes. Parallel measurement of DNA copy number and mRNA levels in cDNA microarrays permits changes in copy number to be compared with transcription levels on a gene-by-gene basis to generate lists of candidate genes within the defining amplicons (Hyman et al, 2002;Pollack et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The present observations of the genes are consistent with our earlier findings, confirming their potential role as biomarkers for early NSCLC. Of the 3 newly characterized genes, ENO1 is located at chromosome 1p36.23 that is one of the most frequent targets of genomic amplification in lung cancer (8,19,20). Racz et al (21) found that ENO1 was amplified in tumors tissues of early stage of NSCLC, especially SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing genomic copy number changes of the genes on sputum by using in situ minichip assay The 15 genes that were identified from our previous work (8,19), whose copy number changes were associated with stage I NSCLC are listed in Table 2. We made probes that specifically covered genomic sequences of the target genes as previously described (7).…”
Section: Patients and Control Subjectsmentioning
confidence: 99%
See 1 more Smart Citation